Hardness testing of five brands of acrylic artificial teeth - Daisy Wulansari; Rasmi Rikmasari; Seto Pramudita (Indonesian Journal of Prosthodontic, 2023)
Acrylic artificial teeth are still widely used in denture fabrication. Several brands marketed in Bandung claimed that their product has met the standard but all the brands do not give the mechanical properties data including hardness. The ADA specification standard no. 15 requires a hardness of minimum 15.00 KHN for acrylic artificial teeth. This study is aimed to find out which acrylic artificial teeth have a standardized hardness value. The study is an analytic descriptive study performed on five brands of acrylic artificial teeth marketed in Bandung. The samples were given 10 indentation spots on the upper and lower surfaces. The results of the study were analysed using Anova test and Dunnet test. The analysis showed that the hardness value of the upper and lower surfaces was as followed, respec-tively: A, 17.95 KHN and 17.46 KHN; B, 17.01 KHN and 17.49 KHN; C, 18.24 KHN and 17.41 KHN; D 17.61 KHN and 17.01 KHN; E 17.01 KHN and 16.59 KHN. The two-ways Anova showed that the hardness value of both sur-faces does not differ significantly. It was concluded that the five brands have met ADA specification standard no. 15 and there were differences in hardness values among the brands.